2015
DOI: 10.1016/j.sbspro.2015.07.125
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Music Interventions to Improve Social Skills in Adolescents with Autism Spectrum Disorders in Integrated Group Music Therapy Sessions

Abstract: The lack of social interest is one of the core features of individuals with Autism Spectrum Disorders (ASD). Individuals with ASD suffer direct and indirect consequences related to their social interaction deficits. The effect of these deficits often increases during adolescence. In this period, adolescents with ASD start to report their desire for peer social interaction, and may also experience more loneliness than their typically developing peers. It is especially vital for adolescents with ASD to have emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 15 publications
(11 reference statements)
2
14
0
4
Order By: Relevance
“…The growing body of evidence on the effectiveness of music-based approaches among children with ASD supports their adoption. Furthermore, this group-based intervention is designed to be more efficient than one-on-one therapy and can therefore be implemented on a larger scale, reaching more of the target population (Eren, 2015). In addition, the peer-to-peer interaction fostered in the VOICSS model supports expressive and pragmatic communication skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing body of evidence on the effectiveness of music-based approaches among children with ASD supports their adoption. Furthermore, this group-based intervention is designed to be more efficient than one-on-one therapy and can therefore be implemented on a larger scale, reaching more of the target population (Eren, 2015). In addition, the peer-to-peer interaction fostered in the VOICSS model supports expressive and pragmatic communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the therapy programs did not have a specific structure and curriculum. However, direct interactions with peers in a group setting have the potential to enhance children’s social skills more than individual music therapy and some research on group-based models has shown promising outcomes (Eren, 2015). For example, LaGasse (2014) found that, compared with children who participated in group sessions on social skills, children in group-based music therapy sessions made greater improvements in joint attention with peers, eye gaze toward others, and parental perception of social skills.…”
mentioning
confidence: 99%
“…They develop the fields of language and communication, emotions, comprehension, physical education, etc. (Eren, 2015) On the question: Do all autistic children love music? All teachers responded that they all love music, but sometimes it depends on their daily mood and other outside factors such as the weather, emotional state, environment, etc.…”
Section: Music Integration In Educational Activities and Inclusion Of Autistic Childrenmentioning
confidence: 99%
“…So far music therapy has been widely used to overcome various problems such as to reduce stress [8]. Music is also used as a medium to improve well-being [6], and as a medium of intervention to develop the abilities of autistic children [9]. In addition, music also provides relaxation media with communication through rhythm, listening to music, non-verbal cues, exploration, movement, and improvisation [10].…”
Section: A Music As a Theurapic Toolmentioning
confidence: 99%